Do submarine canyons influence the structure and diversity of benthic fish assemblages on the continental shelf edge? - Nyawo, Mpilonhle Aura June-Rose (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
Marine ecosystems play an important role in human welfare, such as providing food security and providing social, economic and environmental benefits to an increasing human population. However, due to the deleterious impact of overfishing as well as habitat degradation, pollution and climate change, many marine ecosystems and the substantial biodiversity they support, are under increasing threats. Submarine canyon ecosystems cut into the continental margin in all our oceans and are considered regions of enhanced diversity, abundance and biomass for many marine communities, including fish. In South Africa, the tropical Delagoa Ecoregion is characterised by numerous submarine canyons that are home to coelacanths Latimeria chalumnae, and a variety of commercially important line fish species. However, there is currently a lack of information on the ecological structure and functioning of these canyons, in relation to nearby non-canyon ecosystems. The aim of this thesis was to generate knowledge on the role of submarine canyons in influencing the benthic fish assemblage structure and diversity on the continental shelf and shelf edge within the high-latitude coral reef ecosystems in the tropical Delagoa Ecoregion of South Africa. First, a systematic literature review was conducted to examine the current knowledge on the role of submarine canyons on the benthic fish assemblages occurring on continental margins, as well as outline the trends in canyon research. For the fieldwork component of this thesis, baited remote underwater stereo-video systems were utilised to gather data. The first research chapter, chapter 3, investigated the effect of ecosystem and depth on the diversity and structure of benthic fish assemblages within iSimangaliso Wetland Park in the Delagoa Ecoregion. Data were collected in 2017 from Wright Canyon (canyon ecosystem) and adjacent slope ecosystems around the canyon (non-canyon ecosystem) at depths ranging between 70"“240 m. The second research chapter, chapter 4, data were collected in 2018, from 60"“100 m depths in three ubmarine canyons (Wright, Diepgat,Levens) and their adjacent habitat within iSimangaliso Wetland Park to investigate the diversity patterns and community structure of benthic fish and cons ider location as a factor. The systematic review showed that canyon research is still very much in its infancy, however more papers are expected to be published in the future. There were clear location associated biases detected, with more than 90% of the canyon research being concentrated in the Mediterranean Sea, while only one study was published from South Africa. Most of the reviewed literature focused on invertebrates, with benthic fish (including cartilaginous fish) being the second most studied taxa. A wide range of methods from both fishery- dependent and fishery-independent categories were used to gather the data of benthic fish from the canyons and adjacent areas. With over 8500 submarine canyons mapped globally, the number of submarine canyon research published and the detected location bias is of great concern. More studies are needed in order to understand the role of submarine canyons on adjacent slope habitats Overall, the results from the research chapters indicated that there were higher a bundances in the canyon ecosystem compared to the non-canyon ecosystem. In contrast, evenness and beta-diversity were higher in the non-canyon ecosystem. Relief, bottom type as well as depth played a major role in explaining the observed abundance and diversity patterns. Both evenness and beta-diversity decreased with increase in depth. The canyon and non-canyon also differed in terms of habitat structure. The canyon ecosystem was characterised by patched reef and reef habitats with high relief whereas the non-canyon ecosystem was characterised by flats and habitats, especially at shallower depths. Additionally, there were clear differences in terms of the fish community structure between the canyon and the non-canyon ecosystem. The heterogeneous and complex habitats of the canyon ecosystem were typified by species such as Epinephelus poecilonotus, Polysteganus coeruleopunctatus and Chrysoblephus puniceus in comparison to the less complex habitats outside the canyons that were preferred by species such as Lagocephalus sceleratus, and Rhinobatos leucospilus. The different locations sampled demonstrated that the canyon effect was not onsistent at all locations, with varying results detected in the different sample locations. This research demonstrates that clea r differences exists between the benthic fish assemblages associated with canyon and non-canyon ecosystems and provides important information on the role of submarine canyons in the iSimangaliso Wetland Park. From this thesis, it is clear that a 'canyon effect' exists in the continental shelf and shelf edge. The results suggested that heterogeneity of habitats was the most important environmental factor that differed between the canyon and non-canyon ecosystems and these differences in the habitat were driving the observed patterns. This thesis has provided a reference point, with regards to investigating the role and influence of these canyons on benthic fish assemblages occurring on the continental shelf edge. The information provided by this thesis can ultimately be used in other studies investigating benthic fish assemblages in other submarine canyons within iSimangaliso Wetland Park and the rest of South Africa./
Keywords: Submarine valleys; iSimangaliso Wetland Park (South Africa); Biotic communities -- South Africa -- iSimangaliso Wetland Park; Groundfishes -- South Africa -- iSimangaliso Wetland Park; Marine ecology -- South Africa -- iSimangaliso Wetland Park